Songket Fabric Weaving Training in Empowering Poor Women at Home Industry - Imaniar, Mahrati; Sutarto, Joko; Edy Mulyono, Sungkowo (Journal of Nonformal Education, 2020)
Songket fabric weaving training was conducted to empower poor women with the hope that they can overcome the family economy, acquire skills, and be able to become independent individuals. The objectives of this study were (a) to describe and analyze the program planning of songket fabric weaving training, (b) to describe and analyze the process of songket fabric weaving training, (c) to describe and analyze the success of songket fabric weaving training, (d) describe and analyze inhibiting and supporting factors in songket fabric weaving training. The approach used in this research was qualitative approach. The data were collected through observation, interviews, and documentation. The informants consisted of two tutors and three training participants. The results of this study show that (1) the training program planning was arranged according to the needs of the participants, (2) the training process was directed in accordance with the materials by employing adult learning methods, (3) the success of the training had different achievement standards, (4) internal and external factors became obstacles and supporters of songket fabric weaving training as competence of tutors, enthusiastic participants, assistance from non-governmental, market needs and lack of available tools. Weaving cloth training will be carried out with maximum if the trainer has the ability and spirit in learning. Andragogy learning methods are tailored to the needs of learners. In addition, support from the community in training support. In addition to the training, need to think about the market needs so that the training products can be sold to the community. The benefit of this research is as a reference in conducting the training should use andragogy in learning so that the training according to the needs of students and get results more effective and efficient.